Comparison of Thermobifida fusca Cellulases Expressed in Escherichia coli and Nicotiana tabacum Indicates Advantages of the Plant System for the Expression of Bacterial Cellulases - Klinger, Johannes; Fischer, Rainer; Commandeur, Ulrich (Frontiers in Plant Science, 2015)
The economic conversion of lignocellulosic biomass to biofuels requires in addition to pretreatment techniques access to large quantities of inexpensive cellulases to be competitive with established first generation processes. A solution to this problem could be achieved by plant based expression of these enzymes. We expressed the complete set of six cellulases and an additional β-glucosidase expressed from Thermobifida fusca in the bacterium Escherichia coli and in tobacco plants (Nicotiana tabacum). This was done to determine whether functional enzyme expression was feasible in these organisms. In extracts of recombinant E. coli cells, five of the proteins were detected by western blot analysis, but exocellulases E3 and E6 were undetectable. In the plant-based expression system we were able to detect all six cellulases but not the β-glucosidase even though activity was detectable. When E. coli was used as the expression system, endocellulase E2 was active, while endocellulases E1 and E5 showed only residual activity. The remaining cellulases appeared completely inactive against the model substrates azo-carboxymethyl-cellulose (Azo-CMC) and 4-methylumbelliferyl-cellobioside (4-MUC). Only the β glucosidase showed high activity against 4-MUC. In contrast, all the plant-derived enzymes were active against the respective model substrates. Our data indicate that some enzymes of bacterial origin are more active and more efficiently expressed in plants than in a bacterial host.